1992
DOI: 10.1042/bj2810273
|View full text |Cite
|
Sign up to set email alerts
|

Chain-length dependency of interactions of medium-chain fatty acids with glucose metabolism in acini isolated from lactating rat mammary glands. A putative feed-back to control milk lipid synthesis from glucose

Abstract: The effects of a series of medium-chain fatty acids (C6-C12) on glucose metabolism in isolated acini from lactating rat mammary glands have been studied. Hexanoate (C6) octanoate (C8) and decanoate (C10), but not laurate (C12), decreased [1-14C]glucose conversion into [14C]lipid and the production of 14CO2 (an index of the pentose phosphate pathway). With hexanoate and octanoate, glucose utilization was decreased, whereas decanoate had a slight stimulatory effect on glucose utilization, but there was a large a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…More recently, inhibition of mammary lipogenesis by medium chain fatty acids has been observed (Agius & Williamson, 1980;Heesom et al, 1992). Heesom et al (1992) suggested that FIL may regulate lactose and casein synthesis, whereas fat synthesis may be regulated by a negative feedback mechanism involving medium chain fatty acids.…”
Section: Negative Feedback On Milk Fat Synthesismentioning
confidence: 99%
“…More recently, inhibition of mammary lipogenesis by medium chain fatty acids has been observed (Agius & Williamson, 1980;Heesom et al, 1992). Heesom et al (1992) suggested that FIL may regulate lactose and casein synthesis, whereas fat synthesis may be regulated by a negative feedback mechanism involving medium chain fatty acids.…”
Section: Negative Feedback On Milk Fat Synthesismentioning
confidence: 99%
“…Recent research suggests that autocrine mechanisms appear to control the rate of milk synthesis in rats (Heesom, Souza, Ilic & Williamson, 1992), goats Wilde, Calvert, Daly & Peaker, 1987), marsupials (Sharman, 1970) and women (Prentice, Addey & Wilde, 1989;Daly et al 1993 b). A 7-6 kDa component of the whey fraction of goats' milk (feedback inhibitor of lactation, FIL) has been shown to inhibit the synthesis and secretion of milk by stopping membrane trafficking between the endoplasmic reticulum and the Golgi body (Wilde, Addey, Boddy-Finch & Peaker, 1995).…”
Section: Autocrine Control Of Milk Synthesismentioning
confidence: 99%
“…In fact, many of the initial pathways of FA biosynthesis were defined using mammary tissue from lactating ruminants and rodents (1). The unique feature of FA synthesis in the MG is that saturated FA with 6 -14 carbons constitutes the major product of de novo FA synthesis in these animals (10,38,39). This is because the mammary alveolar cells contain thioesterase II (OLAH), which terminates FA synthesis after the addition of 8 -16 carbons (21).…”
mentioning
confidence: 99%